The Resilience of Pandemic Digital Deliberation: An Analysis of Online Synchronous Forums - Elstub, Stephen; Thompson, Rachel; Escobar, Oliver; Hollinghurst, Joe; Grimes, Duncan; Aitken, Mhairi; McKeon, Anna; H. Jones, Kerina; Waud, Alexa; Sethi, Nayha (Javnost-The Public, 2021)
Quality deliberation is essential for societies to address the challenges presented by the coronavirus pandemic effectively and legitimately. Critics of deliberative and participatory democracy are highly skeptical that most citizens can engage with such complex issues in good circumstances and these are far from ideal circumstances. The need for rapid action and decision-making is a challenge for inclusivity and quality of deliberation. Additionally, policy responses to the virus need to be even more co-ordinated than usual, which intensifies their complexity. The digitalisation of the public sphere may be seen as a further challenge to deliberating. Furthermore, these are stressful and emotional times, making a considered judgement on these issues potentially challenging. We employ a modified version of the Discourse Quality Index to assess the deliberative quality in two facilitated synchronous digital platforms to consider aspects of data use in light of COVID 19. Our study is the first to perform a comprehensive, systematic and in-depth analysis of the deliberative capacity of citizens in a pandemic. Our evidence indicates that deliberation can be resilient in a crisis. The findings will have relevance to those interested in pandemic democracy, deliberative democracy in a crisis, data use and digital public spheres.